2014
DOI: 10.1371/journal.pone.0096980
|View full text |Cite
|
Sign up to set email alerts
|

Combining Site Occupancy, Breeding Population Sizes and Reproductive Success to Calculate Time-Averaged Reproductive Output of Different Habitat Types: An Application to Tricolored Blackbirds

Abstract: In metapopulations in which habitat patches vary in quality and occupancy it can be complicated to calculate the net time-averaged contribution to reproduction of particular populations. Surprisingly, few indices have been proposed for this purpose. We combined occupancy, abundance, frequency of occurrence, and reproductive success to determine the net value of different sites through time and applied this method to a bird of conservation concern. The Tricolored Blackbird (Agelaius tricolor) has experienced la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 19 publications
0
15
0
Order By: Relevance
“…Carrasco et al (2017) showed that colonial nesting herons and egrets strive to strike a balance between nest site fidelity and habitat preferences, suggesting that a colony may not form in a site that had previously been occupied. This has also been observed in tricolored blackbirds, where most colony sites are not used in consecutive years (Beedy and Hamilton 1997;Holyoak et al 2014;Airola et al 2017). This variable site occupancy can make it challenging to re-capture banded birds and/or to collect yearly population count data (Marshall et al 2004).…”
Section: Introductionmentioning
confidence: 65%
“…Carrasco et al (2017) showed that colonial nesting herons and egrets strive to strike a balance between nest site fidelity and habitat preferences, suggesting that a colony may not form in a site that had previously been occupied. This has also been observed in tricolored blackbirds, where most colony sites are not used in consecutive years (Beedy and Hamilton 1997;Holyoak et al 2014;Airola et al 2017). This variable site occupancy can make it challenging to re-capture banded birds and/or to collect yearly population count data (Marshall et al 2004).…”
Section: Introductionmentioning
confidence: 65%
“…While the reproductive success of colonies that breed in alternative habitats have been shown to be similar to, or greater than, those in the traditional wetland habitats, the population continues to decline (Holyoak, Meese, & Graves, 2014;Weintraub, George, & Dinsmore, 2016). Breeding tricoloured blackbirds may have multiple breeding attempts in a single season, potentially at a different site within the same breeding season, and are also not likely to use the same breeding sites each year but seem to prefer the same habitat types (DeHaven, Crase, & Woronecki, 1975).…”
Section: Study Speciesmentioning
confidence: 99%
“…It is not clear whether this movement is facilitated by habitat connectivity between colonies, or whether individuals are simply able to fly over unsuitable habitat en route to a different colony. However, evidence of dwindling site occupancy and recruitment due to habitat loss (Holyoak et al 2014) suggests migration may become more difficult with increasing or prohibitive distances between colonies. Thus, continuing habitat loss could lead (directly or indirectly) to population fragmentation across the Tricolored Blackbird's range, accelerating declines in genetic diversity due to absolute colony loss.…”
Section: Low Genetic Diversitymentioning
confidence: 99%
“…These declines are attributed to 2 primary causes: the widespread loss of the Tricolored Blackbird's native wetland habitat (estimated at a 96% loss over the last 150 years, Kreissman 1991) to agriculture and urbanization (Beedy 2008;Meese et al 2014), and the species' switch to nesting in active grain fields that are harvested as part of normal agricultural operations, which has resulted over several decades in complete losses of many of the largest colonies. Because of land-use changes and fragmentation of suitable habitat, breeding site occupancy of Tricolored Blackbirds has declined 3 times as quickly as sites have been recruited (Holyoak et al 2014).…”
Section: Introductionmentioning
confidence: 99%